Green Corporate Performance Management: A Strategic Approach to Environmental and Organizational Sustainability - Agus Kusnawan; Selamet Riyadi; Setyani Dwi Lestari; Slamet Mudjijah (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Green Corporate Performance Management (GCPM) is a strategic approach aimed at integrating sustainability principles into corporate performance management. This article discusses the critical role of Green Human Resource Management (GHRM) in supporting the implementation of GCPM through the development of policies and practices that promote environmentally friendly behavior, such as green recruitment, sustainability training, green performance management, and green technology innovation. GCPM not only helps companies reduce environmental impacts but also enhances operational efficiency, reputation and competitiveness in the global market. This approach includes cross-functional collaboration and green transformational leadership as key success factors. However, the implementation of GCPM faces challenges, including high initial investments, organizational cultural resistance, and the complexity of measuring green performance. This research provides a systematic review of recent literature, constructs a GCPM process framework, and identifies research gaps. The findings indicate that GCPM offers long-term benefits for both the environment and corporate profitability. By addressing implementation barriers, GCPM can become a strategic model for achieving socially responsible business sustainability while meeting stakeholder needs in the sustainability era. This article also proposes a research agenda to support the theoretical and practical development of GCPM in the future.